Cellular and molecular neurobiology - Hammond, C. (Constance) (Academic Press, 2001)
This Second Edition is the new, thoroughly revised edition of the established and well-respected authoritative text in the field. Cellular and Molecular Neurobiology is hypothesis-driven and firmly based on numerous experiments performed by experts in the field. Seven new chapters (five new and two totally rewritten) complement and expand on the First Edition and are written in a way that encourages students to ask questions. Additionally, new, groundbreaking research data on dendritic processing is presented in a very easy-to-understand format.